Reducing conflict in development and allocation of transboundary rivers - Jalilov, Shokhrukh-Mirzo; Amer, Saud A.; Ward, Frank A. (Eurasian geography and economics, 2013)
This article explores opportunities for water scarcity to motivate neighboring nations in transboundary basins to cooperate in the development and allocation of water. Climate change raises the importance of discovering foundations for this cooperation. We examine the development of infrastructure and allocation of water in the controversial Amu Darya Basin. An analysis is presented that characterizes politically constrained and economically optimized water-use patterns in the basin. Using information on the basin's energy potential, water supplies, land area, crop water requirements, and crop economics, we analyze total basin-wide economic welfare over a 20 year period. Results show that the development and operation of the planned Rogun Dam has the potential to secure agricultural benefits downstream for Afghanistan, Uzbekistan and Turkmenistan, while supplying some winter power upstream in Tajikistan in normal water conditions. Results show that the ongoing conflict in the Amu Darya Basin over water infrastructure and allocation has the potential to be resolved in a way to secure economic gains for all four nations. However, patient and difficult political negotiations will be required to achieve the gains indicated. Данная работа исследует возможности мотивации соседних стран для взаимодействия в развитии и распределении воды по причине дефицита водных ресурсов в трансграничных бассейнах. Изменение климата повышает важность нахождения основ для такого рода кооперации. Мы исследовали развитие инфраструктуры распределения воды в противоречивом бассейне реки Амударья. Рассмотренный анализ характеризует политически ограниченное и экономически оптимизированное распределение воды в бассейне. Используя данные по энергопотенциалу, имеющимся водным и земельным ресурсам, потребностям сельскохозяйственных культур в воде и экономике сельскохозяйственных культур, мы провели анализ совокупного экономического благосостояния в бассейне реки на 20-летний период. Результаты показывают, что функционирование Рогунского водохранилища имеет потенциал для обеспечения сельскохозяйственных выгод для стран низовья: Афганистана, Узбекистана и Туркменистана, в то же время обеспечивая некоторое количество зимней энергии для расположенного выше по течению Таджикистана в годы с нормальной водообеспеченностью. Результаты показывают, что текущий конфликт в бассейне реки Амударья за водную инфраструктуру и распределение имеет потенциал разрешиться путем экономического выигрыша для всех четырех стран. Однако, требуется терпение и сложные политические переговоры чтобы достичь указанных выигрышей.